Shadow of doubt : a thriller [compact disc, unabridged] - Thor, Brad (Thor, Brad. Scot Harvath., 2024)
A shadowy Russian defector. A beautiful Norwegian intelligence officer. A deadly American spy. An ingenious plot to collapse the United States has been uncovered. But can the highly suspect intelligence be trusted? In the fog of war, when friends can appear as enemies and enemies as friends, only one thing is certain, when in doubt, there is no doubt.